Duplication of the Pituitary Gland (DPG)-Plus Syndrome Associated With Midline Anomalies and Precocious Puberty: A Case Report and Review of the Literature - Prezioso, Giovanni; Petraroli, Maddalena; Bergonzani, Michela; Davino, Giusy; Labate, Marialuisa; Ormitti, Francesca; Anghinoni, Marilena; Sesenna, Enrico; Esposito, Susanna (Frontiers in Endocrinology, 2021)
Duplication of the pituitary gland (DPG)-plus syndrome is a rare developmental disorder with few cases described in the literature and characterized by multiple midline and central nervous system malformations. The hypothalamus and hypophysis involvement may be clinically associated with endocrine abnormalities. A 5.9-year-old female child was admitted to our Clinic for premature thelarche and acceleration of growth weight. DPG-plus syndrome with paired infundibula and pituitary glands was diagnosed after birth, when she appeared small for gestational age and she presented with lingual hypoplasia, cleft palate, right choanal stenosis, nasopharyngeal teratoma, and facial dysmorphisms. Neuroimaging revealed a duplication of the infundibula, the pituitary gland, and the dens of the epistropheus despite surgical removal of a rhino-pharyngeal mass performed at the age of two months. An array-CGH revealed a 2p12 deletion. At our evaluation, bone age assessment resulted advanced and initial pubertal activation was confirmed by Gonadotropin-Releasing Hormone stimulation test. Hormonal suppression treatment was started with satisfactory results. This case shows that DPG-plus syndrome must be considered in presence of midline and craniofacial malformations and endocrinological evaluations should be performed for the prompt and appropriate management of pubertal anomalies.